THE AREAS OF MISSPELLING PHONEME IN SANDIAGA UNO’S SPEECH: A PHONOLOGICAL APPROACH - Riel Akmal Ikhsan; Ambalegin Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2020)
This study is chosen to be the main subject in the term of linguistic study due to the popular issue in linguistic area, that is phonology, one of the focused subjects in linguistic aspect in English. Phonology also has several impacts to the people who involve in the language and linguistic subject and matter. Based from the related research, it is about the misspelling phoneme areas in the speech made by a public figure in Indonesia, who is Sandiaga Uno. The main purpose for this research is to find out the areas of misspelling phoneme made by Sandiaga Uno in his speech as the governor candidate for Jakarta, candidate for vice president and also as the public figure in Indonesia. The main result is the phenomenon of misspelling phoneme was existent in the area of dental like the phoneme /ɵ/, area of glottal stop such the sound /ᴅ/, and also the area of stop such the phoneme /ʃ/. This present research will use the phonological approach in linguistic study. Moreover, this present research will use the descriptive qualitative method in analysing and presenting the result of the research. This present research will analyse about the misspelling phoneme areas in phonology study. The data source will be taken from the speech by Sandiaga Uno. The approach that will be used for this present research will be the phonological approach in Linguistics.